Acute sub dural hematoma with extra dural hematoma evacuation in ventricular septal defect patient using conventional craniotomy under local anesthesia following peer regimen - Aziz, Peer Asad; Raja, Riaz Ahmed; Kalhoro, Ali Gohar; Pathan, Sanaullah; Bhand, Muzaffar; Shah, Syed Zeeshan (International Journal of Endorsing Health Science Research, 2017)
Background: Extradural hematoma (EDH), and acute subdural hematoma (ASDH) are common pathologies encountered in neurosurgical emergencies following traumatic injuries usually secondary to road traffic accident, assault and fall. Both extradural hematoma and acute subdural hematoma have dreadful effects on patient’s health if not managed properly and timely and even lead to death. The standard treatment for such problems is conventional large craniotomy under general anesthesia to prevent fatal outcomes. Method: We have presented a case of ASDH with EDH in a patient having history of large ventricular septal defect and due to large ventricular septal defect patient had delay in getting fitness and alongside patient had fallen Glasgow Coma Scale (GCS) which encouraged surgeon to perform the surgery under local anesthesia by following Peer Regimen. Results: The outcome of case turned fruitful and providing possibility of Local anesthesia (Peer Regimen) as an alternate in case of critical emergency to save life of patient. Conclusion: Acute Subdural hematoma with either concomitant ventricular septal defect or alone can evacuated safely under local anesthesia using Peer regimen. Further studies should be carried to know the more benefits of procedure and potential hazards of procedure and to improve outcome from this lethal type of brain injury.